câu 3) a)[tex]x^3+1=(x^2-3x-1)^2<=>x^4-7x^3+7x^2+6x=0<=>x=0\vee x^3-7x^2+7x+6=0<=>(x-2)(x^2-5x-3)=0[/tex]
b)[tex]\left\{\begin{matrix} x^2+4y^2=2<=>(x-2y)^2=2-2xy=1+1-2xy & \\ (x-2xy)(1-2xy)=4 & \end{matrix}\right.\left\{\begin{matrix} a=x-2y & \\ b=1-2xy & \end{matrix}\right.=>\left\{\begin{matrix} a^2=1+b & \\ ab=4 & \end{matrix}\right.=>........[/tex]
câu 4) a) [tex]x^3-x-xy-y=-2<=>x(x-1)(x+1)-y(x+1)=-2<=>(x+1)(x^2+x-y)=-2=1.-2=-1.2[/tex]
b) [tex]T\geqslant \frac{(2+1)^2}{a+b}=9[/tex]
dấu "=" xảy ra khi [tex]\frac{4}{a}=\frac{1}{b}<=>4b=a<=>5b=1=>b=\frac{1}{5}=>a=\frac{4}{5}[/tex]